MENJAGA POLA MAKAN SERTA EDUKASI GIZI PADA ANAK SEKOLAH DASAR - Rizik Habibullah Nurusyaikha; Nana Hendra Cipta; Siti Rokmanah (STKIP Subang, 2023)
Indonesia is currently facing two different nutrition crises due to shifting nutrition. Based on the findings of nutrition screening conducted in a number of elementary schools in Cilincing Subdistrict, North Jakarta, malnutrition occurs in 28% of the population, with the prevalence of obesity being three times greater than underweight. Malnutrition can interfere with normal growth and development of children, increase the risk of disease, and increase hospital costs. After a meeting with the school, it was decided that nutrition education was needed for elementary school students as they had never received nutrition teaching before. The aim of this study was to improve knowledge about balanced nutrition among school-age children and school administrators. In SD Rorotan 03 and SD Rorotan 07, Cilincing sub-district, North Jakarta, the nutrition education was conducted in April 2018 after preparation in March 2018.